Biodiversity of coastal epibenthic macrofauna in Eastern Canadian Arctic: Baseline mapping for management and conservation - Gianasi, Bruno L.; McKindsey, Christopher W.; Archambault, Philippe; Simard, Nathalie; Howland, Kimberly L. (Frontiers in Marine Science, 2022)
Arctic ecosystems are changing rapidly due to global warming, industrial development, and economic growth. However, the ecological consequences for these ecosystems are difficult to predict due to limited knowledge on species abundance, distribution, and biodiversity patterns. This study evaluated the diversity and, assemblage composition of epibenthic macrofauna in shallow coastal areas from five Eastern Arctic locations with increasing economic and shipping activity. Benthic trawls (n=198) were conducted in nearshore coastal habitats of Anaktalak Bay (Labrador), Churchill (Manitoba), Deception Bay (Quebec), Iqaluit (Nunavut), and Milne Inlet (Nunavut), at depths between 3 and 30 m. Diversity and assemblage composition were compared at various taxonomic levels from phylum to species and correlations with broad oceanographic variables were investigated to identify potential drivers of biodiversity. The spatial variability of benthic assemblages was also assessed within each study location. A total of 297,417 macroinvertebrates was identified, belonging to 900 taxa. Abundance and taxonomic richness were highest in Anaktalak Bay. Shannon-Wiener diversity was higher in Anaktalak Bay, Iqaluit, and Milne Inlet than in Churchill and Deception Bay. Churchill showed the lowest diversity metrics among locations. No relationships were observed between diversity and depth, chlorophyll-a, particulate organic carbon, sea surface temperature, or sea ice duration. Assemblages differed among locations at all taxonomic levels, with the highest dissimilarities at the species level; however, dispersion of samples within-groups was significant, suggesting that factors other than locations (e.g., habitat type) influence assemblage composition. While Churchill, Deception Bay, and Iqaluit showed distinct local spatial patterns in diversity metrics and assemblage composition, no patterns were detected in Anaktalak Bay and Milne Inlet. This study represents one of the largest systematic assessments of coastal epibenthic biodiversity in the Canadian Arctic. It identifies patterns of biodiversity and assemblage composition and provides a baseline for studies of community change and the development of informed management and conservation strategies for Arctic coastal ecosystems.